Reality of Electronic Governance with Special Reference to Punjab - Katta, Ashok Kumar (Prabandhan: Indian Journal of Management, 2017)
With the national objective of making India a global empowered nation, the Government of Punjab has also been progressing towards creating a knowledge society by using the power of Information and Communication Technology (ICT). Punjab has started many initiatives in the ICT sector, which aim to deliver huge benefits to the citizens and businesses and also improve the efficiency of government functioning. With the focus on good governance, the Govt. of Punjab aims at the betterment of the lives of its citizens. It is possible only with the advancement in technology with adequate and timely services. It would ensure promptness, openness, and accessibility to the citizens. Considering the above, this paper examined the different e-initiatives by Government of Punjab focusing upon transparency and improved governance in the state by the adoption of e-governance practices. It also attempted to highlight the proficiency of the Government of Punjab to implement as par with the National e-governance plans. The paper further discussed the key areas which need more consideration and responsiveness. A self-designed questionnaire based on a 5- point Likert scale was constructed, and data from a total of 100 respondents was collected and analyzed. Descriptive analysis and correlation were used as the tools for the research analysis. The paper suggested that the government should make people more aware about e-governance initiatives for the successful implementation of its projects.